Heterotic GUT and standard model vacua from simply connected Calabi-Yau manifolds - Blumenhagen, Ralph; Moster, Sebastian; Weigand, Timo (Nuclear physics. B, Particle physics, 2006)
We consider four-dimensional supersymmetric compactifications of the E8×E8 heterotic string on Calabi-Yau manifolds endowed with vector bundles with structure group SU(N)×U(1) and five-branes. After evaluating the Green-Schwarz mechanism and deriving the generalized Donaldson-Uhlenbeck-Yau condition including the five-brane moduli, we show that this construction can give rise to GUT models containing U(1) factors like flipped SU(5) or directly the Standard Model even on simply connected Calabi-Yau manifolds. Concrete realizations of three-generation models on elliptically fibered Calabi-Yau manifolds are presented. They exhibit the most attractive features of flipped SU(5) models such as doublet-triplet splitting and proton stability. In contrast to conventional GUT string models, the tree level relations among the Standard Model gauge couplings at the GUT scale are changed.